THE The Effect of Gender Diversity of the Board of Directors and Board of Commissioners on Dividend Payment Policy - H, Andre Steven; Marheni, Dewi Khornida (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The purpose of this study is to analyze the effect of the proportion of female directors, the proportion of female commissioners, female independent directors, and female independent commissioners on dividend payment policy in Foods and Beverages companies listed on the Indonesia Stock Exchange in 2019-2023. In this study, dividend payment policy is the dependent variable, the proportion of female directors, the proportion of female commissioners, female independent directors, and female independent commissioners are independent variables. The sample used 18 Foods and Beverages companies in 2019-2023. Data for this variable was collected from the website www.idx.go.id in the form of company financial report data. This research method uses multiple linear analysis. The results of the study indicate that partially the proportion of female directors, the proportion of female commissioners, female independent directors, and female independent commissioners have a positive and significant effect on dividend payment policy. The results of this study provide important implications, companies that make dividend payments will provide benefits for both investors and companies. Among them are increasing shareholder trust, influencing stock prices, showing the company's financial performance, and influencing the company's value.